Bridging research and practice: a pilot trial of an adapted social skills program for autism in public services - Mairena, Maria A.; Alcover, Carlota; Arias-Pujol, Eulàlia; Díez-Juan, María; Mezzatesta Gava, Marcela; Elias, Neus; Sentenach, Ares; Elias, Maria; Piera, Eulàlia; González, Mireia; Solomon, Marjorie; Aranbarri, Aritz (Frontiers in Psychiatry, 2025)
BackgroundAutism Spectrum Disorder (ASD) is marked by significant challenges in social communication and interaction, often accompanied by comorbid neurodevelopmental and mental health conditions such as anxiety and depression. These social difficulties can interfere with the development of pragmatic language use, social problem-solving abilities and quality of life. Social skills interventions have shown promising results in addressing these challenges, yet there is a need to adapt such programs for broader, publicly funded settings to enhance accessibility and effectiveness.ObjectiveThis study reports on a randomized, waitlist-controlled pilot efficacy trial evaluating an adapted version of the Social Adjustment Enhancement Intervention Program implemented in a university-affiliated public mental health hospital.MethodsA 10-session group-based intervention was delivered to 79 autistic participants aged 8–17 years. Social behaviors were assessed before and after the intervention using structured observational methodology, and comorbid internalizing symptoms were measured via parent-report standardized questionnaires.ResultsSignificant improvements were observed in the subgroup of children and in participants with higher verbal IQ, particularly in eye contact and functional communication, as measured through observational methodology. Additionally, a reduction in internalizing symptoms was found among children in the experimental group. In the full sample, no statistically significant effects were observed, although trends in the same direction were noted.ConclusionsFindings support the feasibility and pilot evidence of intervention effects of this adapted social skills program, particularly for younger autistic individuals and those with higher verbal abilities. The results underscore the importance of tailoring interventions to age and cognitive profiles, and highlight the value of accessible, evidence-based approaches in public mental health systems. Further research is needed to optimize intervention design and evaluate long-term outcomes.